Optimizing Legal Protection for Women in Early Age Unregistered Marriages: A Socio Legal Analysis in Indonesia - Winestia, Agtian; Husaini, Akhmad; Azhim, Fauzul (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2026)
The practice of unregistered or sirri marriages among children remains prevalent across various regions in Indonesia, driven by economic pressures, low levels of education, as well as the strong influence of socio-cultural norms and religious understanding within the community. Although this practice strictly contradicts Law Number 16 of 2019 concerning Marriage and Law Number 35 of 2014 concerning Child Protection, these marriages continue to take place without administrative recognition from the state. This research aims to thoroughly analyze the forms of legal protection for women bound in early-age sirri marriages and to explore strategies for optimizing this protection within the Indonesian legal system.  This study employs a normative juridical research method using a statutory approach and literature review. The findings reveal that the absence of marriage registration fundamentally weakens women's legal standing, making them highly vulnerable to losing their rights to joint property, spousal support, and child legitimacy, as well as losing protection and access to justice against threats of domestic violence. Additionally, the lack of biological and mental readiness triggers significant reproductive health risks and high psychological burdens.  Therefore, optimizing legal protection can be achieved through comprehensive preventive and rescue strategies. These steps include massive education and socialization regarding the urgency of marriage registration, family economic empowerment, the proactive involvement of the Office of Religious Affairs (KUA) and religious leaders, and the establishment of a holistic support environment. Furthermore, tightening the criteria for granting marriage dispensations by the court, strictly enforcing the law against underage marriage prohibitions, and facilitating marriage confirmation (isbat nikah) applications are essential keys to ensuring comprehensive legal certainty.